CT-angiography source images indicate less fatal outcome despite coma of patients in the Basilar Artery International Cooperation Study. Issue 2 (February 2017) - Pallesen, Lars P; Khomenko, Andrei; Dzialowski, Imanuel; Barlinn, Jessica; Barlinn, Kristian; Zerna, Charlotte; van der Hoeven, Erik JRJ; Algra, Ale; Kapelle, L Jaap; Michel, Patrik; Bodechtel, Ulf; Demchuk, Andrew M; et al.
Background: Coma is associated with poor outcome in patients with basilar artery occlusion. Aims: We sought to assess whether the posterior circulation Acute Stroke Prognosis Early CT Score and the Pons-Midbrain Index applied to CT angiography source images predict the outcome of comatose patients in the Basilar Artery International Cooperation Study. Methods: Basilar Artery International Cooperation Study was a prospective, observational registry of patients with acute basilar artery occlusion with 48 recruiting centers worldwide. We applied posterior circulation Acute Stroke Prognosis Early CT Score and Pons-Midbrain Index to CT angiography source images of Basilar Artery International Cooperation Study patients who presented with coma. We calculated adjusted risk ratios to assess the association of dichotomized posterior circulation Acute Stroke Prognosis Early CT Score (≥8 vs. <8) and Pons-Midbrain Index (<3 vs. ≥3) with mortality and favourable outcome (modified Rankin Scale score 0–3) at one month. Results: Of 619 patients in the Basilar Artery International Cooperation Study registry, CT angiography source images were available for review in 158 patients. Among these, 78 patients (49%) presented with coma. Compared to non-comatose patients, comatose patients were more likely to die (risk ratios 2.34; CI 95% 1.56–3.52) and less likely to have a favourable outcome (risk ratios 0.44; CI 95% 0.24–0.80). Among comatose patients, a Pons-Midbrain Index < 3 was related to reduced mortality (adjusted RR 0.66; 95% CI 0.46–0.96), but not to favourable outcome (adjusted RR 1.19; 95% CI 0.39–3.62). Posterior circulation Acute Stroke Prognosis Early CT Score dichotomized at ≥ 8 vs. <8 was not significantly associated with death (adjusted RR 0.70; 95% CI 0.46–1.05). Conclusion: In comatose patients with basilar artery occlusion, the extent of brainstem ischemia appears to be related to mortality but not to favourable outcome.